Pemanfaatan Dana Desa Untuk Ketahanan Pangan Melalui Peran Bumdes di Desa Rioribati Kecamatan Jailolo Selatan - Ruliyanto Syahrain; Musdar Muhammad; Rinto Syahdan (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Rioribati village, Bumdes has been formed but there are problems to run Bumdes in the village, the role of bumdes is very important to provide food security to the village, Rioribati village is known as a non-coastal village.The methods used in this devotion are; Lectures, Practices and Mentoring Participants.Results of Service; Various problems faced by the Rioribati village government, regarding the management of village fund finances for the progress of the village with food, this was also conveyed by the village government who was present at the activity; Rioribati village is a village whose residents work in the agricultural sector; namely plantations, plantation products in Rioribati village have not been utilized properly, many plantation agricultural products have not generated village income and the management of these plantation products produces a product to be sold in the market to generate added value among the Rioribati community